Adsorbed gas density model and re-understanding of gas adsorption behavior in coal seam - Shouya WU; Weiguo LIANG (Meitan xuebao)
Clarifying the adsorbed gas density of coal seam is the basis of studying the adsorption characteristics and the real gas content of coalbed methane, but the existing calculation methods of adsorbed gas density do not reflect the influence of temperature and pressure. Based on the analysis of the potential energy of gas intermolecular interaction and gas-solid molecular interaction, a non-uniform distribution model of gas density near the wall was constructed, and then the calculation equations of adsorption thickness and adsorption layer number were obtained. Then the calculation model of adsorbed gas density was derived, and corresponding adsorption model was established. The reliabilities of the proposed models have been verified by molecular dynamic simulation results and adsorption experimental results. The analysis results show that the adsorbed gas density is greatly affected by gas-solid interaction strength, pressure, and temperature. The stronger the gas adsorption capacity of coal, the greater the gas-solid interaction strength, the higher the gas density near the wall, the higher the adsorbed gas density, and the larger the adsorbed layer number. The region with 1 molecular layer thickness away from the wall is the strong adsorption region, and the main factor affecting the adsorption behavior in this region is gas-solid interaction; the region with more than 1 molecular layer thickness away from the wall is the weak adsorption region, and the main factor affecting the adsorption behavior in this region is external pressure. The gas density near the wall increases with the pressure ascending, and the gas adsorption process is to fill the strong adsorption region first and then to fill the weak adsorption region. Adsorbed gas density and free gas density both increase with the increase of pressure, but the adsorbed gas molecular layers’ number will decrease. The excess adsorption capacity shows a decreasing or stable trend with the ascent of pressure, as a result of the combined action of adsorbed gas density and molecular layers’ number. With the temperature increasing, adsorbed gas density, free gas density, adsorbed gas molecular layers’ number and thickness, and the absolute and excess adsorption capacity all show a downtrend, but the gas density in the range of 0.2 nm near the wall is less affected by temperature. Therefore, assisted by the desorption methods of reducing pressure and rising temperature, reducing the intensity of gas-solid interaction can further reduce the gas absolute adsorption capacity. In addition, the decrease in gas adsorption layers’ number caused by the effect of rising temperature and increased pressure is the reason for the decline in the proportion of adsorbed gas in deep coal seams.